Factory logistics improvement projects: Case Northern Thailand - Sakgasem Ramingwong (2018)
© Springer-Verlag Berlin Heidelberg 2015. The paper analyses and discusses the interest and results from 3-years factory logistics improvement projects in 75 factories in Northern Thailand region. Funded by government agency, the consultant had conducted man-days of consultancy for the factory, aiming at improving logistics efficiency or reduce logistics cost. However, with limited resource, only top priority problem can be chosen. Where the size and type of industry varies, the problem, approach and result are different as expected. Therefore, it is interesting to understand the nature of the factory and their selected project type.